¿Puede el arte ser definido? : controversias sobre la definición del arte en la estética contemporánea y la propuesta de Arthur C. Danto - Parselis, Verónica (Sapientia, 2008)
In the contemporary aesthetics, particularly in the analityc context , there is a strong preeminence of an anti-essencialist tendency i n relation to the posibility of a definition of art . Arthur C . Danto reacts against this tendency, and he proposes since his early writings the search of a definition of art . This article summarizes thi s discussion in contemporary philosophy, then shows Danto 's controversial position as an essenrialrst and, finally, explains the definition of art reached by this philosopher.